2000
DOI: 10.1128/jb.182.14.3904-3912.2000
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Control of the Citrate-Inducible citMCDEFGRP Operon, Encoding Genes Involved in Citrate Fermentation in Leuconostoc paramesenteroides

Abstract: In this study we describe the expression pattern of the Leuconostoc paramesenteroides citMCDEFGRP operon in response to the addition of citrate to the growth medium. An 8.8-kb polycistronic transcript, which includes the citMCDEFGRP genes, was identified; its synthesis was dramatically induced upon addition of citrate to the growth medium. We also found that expression of the cit operon is subjected to posttranscriptional regulation, since processing sites included in four complex secondary structures (I, II, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
40
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 22 publications
2
40
0
Order By: Relevance
“…The answer is provided by the different induction profiles of the citrate metabolic pathways in Leuconostoc and Lactococcus species. In Leuconostoc mesenteroides, the enzymes of the pathway are induced by the presence of citrate in the medium, while in L. lactis, the induction additionally requires a low pH in the medium, suggesting a role in acid stress (40,85,89,92,93,95). The conversion of carbohydrate to lactic acid results in acidification of the medium, which eventually inhibits growth.…”
Section: Physiological Functionmentioning
confidence: 99%
“…The answer is provided by the different induction profiles of the citrate metabolic pathways in Leuconostoc and Lactococcus species. In Leuconostoc mesenteroides, the enzymes of the pathway are induced by the presence of citrate in the medium, while in L. lactis, the induction additionally requires a low pH in the medium, suggesting a role in acid stress (40,85,89,92,93,95). The conversion of carbohydrate to lactic acid results in acidification of the medium, which eventually inhibits growth.…”
Section: Physiological Functionmentioning
confidence: 99%
“…The citM gene from W. paramesenteroides [11] and L. lactis [12] and mae gene from Lc. mesenteroides [22] were described as potentially encoding the oxaloacetate decarboxylase.…”
Section: Expression Of Citm In L Lactismentioning
confidence: 99%
“…Transcriptional analysis showed that in W. paramesenteroides, the genes encoding the citrate permease (citP), the citrate lyase complex (citDEF) and a putative ME (citM) are transcribed in a polycistronic unit (citMCDEFGRP) thus constituting the cit operon. The expression of this operon is increased in the presence of citrate [11]. In L. lactis CRL264, the citrate utilization genes are organized in two different operons: a chromosomal cit operon including the genes citM-CDEFXG (in a molecular organization similar to W. paramesenteroides) and a plasmidic operon including the citP gene.…”
Section: Introductionmentioning
confidence: 99%
“…Despite that, no regulator involved in the control of the expression of citrate utilization genes has been characterized in LAB. The dairy Weissella paramesenteroides J1 carries the cit operon, which includes the genes encoding the oxaloacetate decarboxylase (citM), the citrate lyase active complex (citCDEFG), and the citrate permease (citP) (14) (Fig. 1A), which are key proteins involved in the citrate fermentation pathway.…”
mentioning
confidence: 99%
“…Among them, only DeoR has been purified and has had its interactions with its operators investigated (24). In a previous study, we demonstrated that the transcription of the citI gene and the cit operon is induced when the J1 strain is grown in the presence of citrate (14). Overexpression of CitI in Escherichia coli resulted in trans activation of the Pcit promoter, suggesting that CitI is a transcriptional regulator (14).…”
mentioning
confidence: 99%